Yew poisoning of olive baboons (Papio anubis) in captivity: laboratory diagnosis - Kominkova, Marketa; Stanisavljevic, Maja; Zitka, Ondrej; Mazanek, Stanislav; Sedlackova, Jana; Bandouchova, Hana; Pikula, Jiri; Beklova, Miroslava; Kizek, Rene (Neuro endocrinology letters, 2013)
OBJECTIVES: Toxic effects of the yew have been known since ancient times. Yew toxicity is due to the content of cyanogenic glycosides and a mixture of alkaloids known as taxines. Taxine B is probably responsible for the most part of adverse effects in poisoned organisms. This particular taxoid is common in body fluids of the yew-poisoned. The present study is engaged with laboratory examination to confirm substances that lead to fatality of a pair of olive baboons (Papio anubis) following ingestion of yew seeds. When both cage mates (male and female) died suddenly, poisoning was suspected because many berries had fallen into the cage from a nearby fruiting yew tree (Taxus baccata) during the windy night before. METHODS: The analysis was performed using electrospray ionization quadrupole time-of-flight mass spectrometry. A flow injection analysis/mass spectrometry setting was prepared for this purpose. RESULTS: The above mentioned mass spectrometry analysis of taxoids confirmed poisoning by taxanes. The presence of taxin B/isotaxin B was confirmed in all investigated samples. Apparently in urine and bile there were concentrations ranging 150-220 ng.mL-1 and in blood serum concentrations 25-30 ng.mL-1. CONCLUSION: It follows from the results obtained that we confirmed that baboons were deadly intoxicated by yew fruits.
Keywords: fatální výsledek; Alkaloids; alkaloidy; zvířata v ZOO; tis; Bile; Blood Chemical Analysis; Female; klinické laboratorní techniky; zvířata; Papio anubis; nemoci opic; ženské pohlaví; Animals, Zoo; Male; Taxoids; nemoci přenášené potravou; taxoidy; Clinical Laboratory Techniques; biochemická analýza krve; Taxus; žluč; Animals; Fatal Outcome; mužské pohlaví; Monkey Diseases; Foodborne Diseases